Reliability of resting energy expenditure in major burns: Comparison between measured and predictive equations. Issue 6 (December 2019) - Jeon, Jinwoo; Kym, Dohern; Cho, Yong Suk; Kim, Youngmin; Yoon, Jaechul; Yim, Haejun; Hur, Jun; Chun, Wook
Summary: Background & aims: Poor outcomes can result from inadequate energy intake. We aimed to investigate the reliability of resting energy expenditure (REE) measured by indirect calorimetry (IC) with REE calculated using predictive equations for nutritional support in patients with major burns. Methods: REE was measured using IC and compared with predictive equations in 215 adult severe burns patients from Jan 2011 to Jun 2015. Agreement between IC and predictive equations was assessed using Bland–Altman methods. Results: All predictive equations, including newly developed Hangang equation, were compared with REE measured using IC. The mean measured REE was 1712 kcal/d. Bland–Altman analysis showed that 1.2 times HBE, Thumb 25, and Ireton–Jones equations had higher accuracy and reliability. The concordance correlation coefficient was higher (0.49) in the Ireton–Jones equation, and root mean square error (RMSE) was lowest (471.5) in the Thumb 25 equation. The proportion of patients with predicted REE within ±10% of measured REE was highest with Thumb 25 (52.5%). In the validation set, the Hangang equation showed the highest Lin's concordance correlation coefficient (0.67) and the lowest RMSE (311.4). Other equations for burns patients had higher mean bias and overestimated REE when compared with IC results. Conclusions: This study suggests that Thumb 25 can be used as an alternative method for estimating energy requirements of patients with major burns when IC is not available or applicable. However, for these patients with significant variation in metabolism over time, an alternative equation is the new Hangang equation.